THE DIFFICULTIES OF EFL TEACHERS IN USING DIALOGUE JOURNAL IN TEACHING WRITING - Hamidah, Alfi (Universitas Islam Lamongan, 2016)
This study is aimed to identify the difficulties faced by EFL teachers in teaching writing process using dialogue journal at 7 th grade of SMP N 1 Kembangbahu Lamongan and to describe how the teachers solve their teaching writing process problems using dialogue journal.Keywords: A Dialogue Journal, Teaching Writing